Analisis Konsentrasi Dan Penyebaran Debu Jatuh (Dustfall) Di Pemukiman Sekitar Pabrik Pengolahan Crude Palm Oil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Crude Palm Oil (CPO) processing plant PT.Z Pelalawan Regency is one of the palm oil processing factories that uses palm kernel shell fuel and palm fiber as an energy source. Pal oil processing is certainly in the environment, pollutant gases and dust. This research to analyse the concentration and distribution of dustfall from the pollutant source. Sampling of dustfall using a dustfall collector based on SNI 13-4703-1998. Variation of dustfall sampling distance 0 m, 300 m, 1230 m from the pollutant source. The results showed that the highest concentration of dustfall wa at distance of 0 m, from the pollutan souerce with an average value of 24,46 g/m2/month at a distance of 0 m from the pollutant source and the lowest at distance of 1230 m wit an average value of 5,13 g/m2/month.Keyword : Shell, Fiber Distance, Palm Oil Mill